FACTORS RELATED TO CONTINUATION OF MANGO CULTIVATION - Rachmah, Alisabela Dhiya; Rasmikayati, Elly; Saefudin, Bobby Rachmat (Universitas Djuanda, 2019)
Usually, commodities shift occurs from food crops to commercial crops, such as horticulture with the aim of improving the welfare of farmer’s life. However, a different situation happened in Sedong Subdistrict, Cirebon Regency where mango farmers switched to paddy cultivation which is a non commercial crop. Most mango farmers began to abandon mango cultivation and made paddy cultivation as their main livelihood. Therefore this research aimed at analyzing the factors underlying the farmer’s decisions to abandon or continue mango cultivation and describing the potential and constraints of mango cultivation. Samples taken were 65 farmers in Sedong Subdistrict, Cirebon Regency consisting of 30 present-grower of mango who also experienced paddy cultivation and 35 past-grower of mango who switched to paddy cultivation. The research method used is the survey research method with data analysis using descriptive statistics and crosstabulation analysis with the fisher exact test. The results showed that the factors related to the farmer's decision to abandon or continue mango cultivation consisted of age, farmer's perception of mango cultivation, risk taking attitude, land tenure status, land area, and farmer group membership. Mango farming has easy transportation in the marketing activities provided by traders, as well as ease of access to credit bunt only for large scale farmers. The constraints felt by farmers in conducting mango farming consist of limited capital for small farmers,